Model poverty reduction through social and economic institutional empowerment of poor communities in South Sulawesi - Nujum -; Annas Plyriadi; Ramlawati Ramlawati (Indonesia Prime, 2017)
This research aims (1) to reviewing the extent to which the role of the Government in implementing the model of empowerment of marginal/poor communities through mentoring program in learning, (2). Reviewing and explain the benefits of implementing the poor's empowerment program to alleviate poverty, (3). To review how to implement the poverty alleviate model that is more in line with the local wisdom of the people of South Sulawesi.The Research results show that (1). Institutional social and institutional Economics that exist in the community in the region Mamminasata South Sulawesi in generally not have the ability to empower the community because it has not received optimal support from the government and private. (2). In general, the education and skills of the community are still low so that people face limitations in living their lives, especially in economic activities, so tend to be unproductive and powerless and become poor.